Commuting and sickness absence - Laszlo Goerke; Olga Lorenz (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
We investigate the causal effect of commuting on sickness absence from work using German panel data. To address reverse causation, we use changes in commuting distance for employees who stay with the same employer and who have the same residence during the period of observation. In contrast to previous papers, we do not observe that commuting distances are associated with higher sickness absence, in general. Only employees who commute long distances are absent about 20% more than employees with no commutes. We explore various explanations for the effect of long distance commutes to work and can find no evidence that it is due to working hours mismatch, lower work effort, reduced leisure time or differences in health status.
Keywords: I10; J22; R2; R40; 330; sickness absence; absenteeism; commuting; health; labour supply